2020
DOI: 10.3390/microorganisms8111818
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress in Patients with Autoimmune Arthritis during the COVID-19 Induced Lockdown in Italy

Abstract: Lockdowns imposed by governments worldwide as a way to limit the spread of severe atypical respiratory syndrome-coronavirus-2 (SARS-CoV2) have had heavy psychological and economic consequences. Arthritis patients are a vulnerable population at an increased risk of peritraumatic stress. This could be due to several reasons, including the fear of shortage of medicine and difficulty receiving periodical medical checks. In the present case-control study, psychological distress in patients with autoimmune arthritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 62 publications
(124 reference statements)
1
21
1
Order By: Relevance
“…In another study from Italy Diamanti et al investigated psychological distress in 100 patients with autoimmune arthritis and 100 controls during the Covid-19 pandemic. They found that the percentages of increased stress scores (46% vs 32%), depression (42% vs 36%) and anxiety (38% vs 25%) of arthritis patients were significantly higher than controls [ 30 ]. In our study group, 46.2% of kidney transplant recipients had high-perceived stress related to Covid-19, 44.3% of the patients had depression, 23.6% of the patients had anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In another study from Italy Diamanti et al investigated psychological distress in 100 patients with autoimmune arthritis and 100 controls during the Covid-19 pandemic. They found that the percentages of increased stress scores (46% vs 32%), depression (42% vs 36%) and anxiety (38% vs 25%) of arthritis patients were significantly higher than controls [ 30 ]. In our study group, 46.2% of kidney transplant recipients had high-perceived stress related to Covid-19, 44.3% of the patients had depression, 23.6% of the patients had anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, throughout the COVID-19 pandemic, physicians and patients have developed several concerns on the use of immune-modulating therapies in patients with IMIDs, mainly due to their ability to increase the risk of infectious disease. In addition, logistical difficulties in reaching the hospitals for continue therapy has been showen [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a main challenge is whether to modify/suspend the ongoing immunosuppressive treatment in IMID patients; clinicians indeed have to consider both the potential risk of an increased infectious exposure and that of disease relapse induced by therapy suspension. The management of IMID patients during the COVID-19 pandemic has become significantly more complex for other reasons such as the limited access to primary care or the contradictory messages on the protective/causative role of the immunosuppressor for SARS-CoV-2, which can fuel psychological distress and lead to a reduction in compliance and adherence to the immune-suppressor therapy [ 7 ]. For these reasons, we aim to study the risks of infections, hospitalizations, or mortality related to COVID-19 in a cohort of patients with rheumatoid arthritis (RA), psoriasis (PSO), or inflammatory bowel diseases (IBD).…”
Section: Introductionmentioning
confidence: 99%
“… 7 - 9 Higher psychological distress related to the COVID-19 pandemic were reported among patients with autoimmune arthritis in Italy. 10 However, studies examining psychological impact in patients with rheumatic diseases are limited globally and none in Malaysia.…”
Section: Introductionmentioning
confidence: 99%